Mortality and Severity in COVID-19 Patients on ACEIs and ARBs—A Systematic Review, Meta-Analysis, and Meta-Regression Analysis - Singh, Romil; Rathore, Sawai Singh; Khan, Hira; Bhurwal, Abhishek; Sheraton, Mack; Ghosh, Prithwish; Anand, Sohini; Makadia, Janaki; Ayesha, Fnu; Mahapure, Kiran S.; Mehra, Ishita; Tekin, Aysun; et al. (Frontiers in Medicine, 2022)
Purpose: The primary objective of this systematic review is to assess association of mortality in COVID-19 patients on Angiotensin-converting-enzyme inhibitors (ACEIs) and Angiotensin-II receptor blockers (ARBs). A secondary objective is to assess associations with higher severity of the disease in COVID-19 patients. Materials and Methods: We searched multiple COVID-19 databases (WHO, CDC, LIT-COVID) for longitudinal studies globally reporting mortality and severity published before January 18th, 2021. Meta-analyses were performed using 53 studies for mortality outcome and 43 for the severity outcome. Mantel-Haenszel odds ratios were generated to describe overall effect size using random effect models. To account for between study results variations, multivariate meta-regression was performed with preselected covariates using maximum likelihood method for both the mortality and severity models. Result: Our findings showed that the use of ACEIs/ARBs did not significantly influence either mortality (OR=1.16 95% CI 0.94 to 1.44, p= 0.15, I2 = 93.2%) or severity (OR=1.18, 95% CI 0.94 to 1.48 p= 0.15, I2 = 91.1%) in comparison to not being on ACEIs/ARBs in COVID-19 positive patients. Multivariate meta-regression for the mortality model demonstrated that 36% of between study variations could be explained by differences in age, gender, and proportion of heart diseases in the study samples. Multivariate meta-regression for the severity model demonstrated that 8% of between study variations could be explained by differences in age, proportion of diabetes, heart disease and study country in the study samples. Conclusion: We found no association of mortality or severity in COVID-19 patients taking ACEIs/ARBs.